Assortments and prices in online grocery retailing - Svetlana Fedoseeva; Roland Herrmann (Digital Business, 2023)
Grocery retailing is undergoing rapid changes. New store formats and market channels, the entry of additional large players, and increasing multichannel activities on the supply side are accompanied by heterogeneous and changing consumer preferences. Retailers are increasingly competing in both price and variety. The question arises: how do product assortments affect retailers' prices? Larger assortments may be attractive for consumers who derive utility from variety or search for niche products. Retailers with a deeper assortment might be in a position to realize higher prices. Our study is the first to quantify the assortment-depth elasticity of price in online retailing, and the magnitude of assortment depth at which a further expansion of the assortment may no longer allow for a higher average price level. We collect a unique dataset for major online full-assortment grocery retailers in Germany and show that an increasing depth of grocery assortment raises online prices. The depth elasticity of price is below unity, and the influence is nonlinear.
Keywords: 650; Online prices; Assortment strategies; Grocery retailing; Product variety; Germany